Carcass wrote:
If \(\frac{(x+2)(x-5)}{(x-3)(x+4)}=1\), then \(x=\)
A. \(-2\)
B. \(- \frac{1}{2}\)
C. \(1\)
D. \(\frac{1}{2}\)
E. \(2\)
Kudos for the right answer and explanation
Take: \(\frac{(x+2)(x-5)}{(x-3)(x+4)}=1\)
Multiply both sides of the equation by \((x-3)(x+4)\) to get: \((x+2)(x-5)=(x-3)(x+4)\)
Expand and simplify both sides to get: \(x^2-3x-10=x^2+x-12\)
Subtract \(x^2\) from both sides to get: \(-3x-10=x-12\)
Add 12 to both sides to get: \(-3x+2=x\)
Add \(3x\) to both sides to get: \(2=4x\)
Solve: \(x = \frac{2}{4}=\frac{1}{2}\)
Answer: D
Cheers,
Brent